Advanced Digital Technologies and their Implications in Oral Surgery: Latest Trends and Innovations - Bouslama, Ghada; Boukhris, Hanen; Zidani, Hajer; Salah, Kawther Bel Haj; Walha, Lamia; BenYoussef, Souha (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Aim: This chapter aims to explore the integration of digital technologies in oral surgery, examining their impact on diagnosis, treatment planning, surgical execution, and overall patient experience. It focuses on the adoption of intraoral scanners, 3D imaging technologies, and computer-aided design and manufacturing systems, with a specific look at how these tools are transforming clinical workflows and surgical outcomes. Methodology: A comprehensive review of current literature and case reports was conducted to evaluate the clinical applications of digital tools in oral surgery. This includes the use of intraoral scanners, cone-beam computed tomography (CBCT), 3D virtual surgical planning, augmented reality, and artificial intelligence. Additionally, the development and use of 3D-printed surgical guides and custom implants were explored to assess their efficacy in improving surgical precision and reducing complications. Results: The integration of digital technologies into oral surgery has resulted in significant advancements in the accuracy and efficiency of procedures. The use of intraoral scanners and CBCT allows for the creation of highly detailed 3D virtual models of a patient's oral anatomy, enabling precise pre-operative planning. Virtual simulations of surgical procedures help identify potential risks and improve decision-making. The employment of 3D-printed surgical guides has enhanced surgical precision, minimizing tissue damage. Moreover, augmented reality tools have facilitated real-time visualization during surgery, further improving accuracy. These advancements have been associated with improved patient outcomes, including reduced post-operative pain, swelling, and recovery time due to the shift toward minimally invasive techniques. Conclusions: Digital technologies have significantly transformed oral surgery, enhancing both the precision of surgical procedures and the overall patient experience. The integration of these technologies offers numerous advantages, including improved diagnosis, customized surgical planning, and the ability to perform minimally invasive surgeries. However, the adoption of these innovations also presents challenges, including the need for specialized training and the high costs associated with new technologies. Continued advancements in artificial intelligence, robotics, and augmented reality hold promise for further elevating the capabilities of oral surgery.